Characterization and effect of using cotton methyl ester as fuel in a LHR diesel engine - Hazar, Hanbey (Pergamon-Elsevier Science Ltd, 2011)
In the present study, surfaces of cylinder head, piston, exhaust and inlet valve of a four-stroke, direct injection, single cylinder diesel engine were coated with molybdenum (Mo) by plasma spray method. Thus, thermal barrier characteristic was brought to these parts. Variances in performance and emission values of cotton methyl ester and 2D fuel mixtures were studied in the ceramic coated and uncoated engines under the same running conditions. Performance (6.0% for specific fuel consumption) and emission values (up to 18.0% for CO, 8.0% for smoke density) of the test fuel were improved in the coated engine compared with the uncoated engine. NO(x) increase (4.5%) with the increased temperatures expected in the coated engine. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Exhaust emissions; Diesel engine; Low heat rejection engines; Methyl ester